Implementasi Program Bakti Inovasi Mengenai Re-Branding Dan Digital Marketing Pada UMKM Kelurahan Bendo - Zainal Abidin Achmad; Nurul Widji Triana; Dewi Puspa Arum; Zalfa Nurrahmah Agustina; Jelita Arinal Haq (Universitas Katolik Widya Karya Malang, 2023)
The use of digital technology which is still low and the lack of knowledge in utilizing branding efforts as an effort to introduce products to consumers are still obstacles faced by UMKM Berkah Soybean Crackers. UMKM Kerupuk Soybean Berkah only focuses on product trading but still has not implemented good product branding. UMKM business actors have not fully implemented digital marketing by utilizing social media so that they do not support the expansion and market reach of the products they produce. LPPM lecturers and KKN students collaborated in the Community Service Innovation Program which was carried out by holding training and socialization activities related to product branding strategies and the use of digital marketing in supporting business stability and reaching a wider market. The implementation method is carried out offline which is offered by business actors and some of their workers. The results of the community service activities obtained by UMKM business participants are satisfied with the material presented and increasing awareness of the importance of using product branding as the spearhead of the products produced as well as training in making logos as a product branding effort by practicing directly has increased the ability to make attractive product branding in accordance with the wishes so as to create consumer loyalty to the products produced